2019
DOI: 10.1093/neuonc/noz023
|View full text |Cite
|
Sign up to set email alerts
|

A low percentage of metastases in deep brain and temporal lobe structures

Abstract: Background. Whole-brain radiotherapy (WBRT) in patients with brain metastases (BM) is associated with neurocognitive decline. Given its crucial role in learning and memory, efforts to mitigate this toxicity have mostly focused on sparing radiation to the hippocampus. We hypothesized that BM are not evenly distributed across the brain and that several additional areas may be avoided in WBRT based on a low risk of developing BM. Methods. We contoured 2757 lesions in a large, single-institution database of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…We found that the proportion of observed BMs in lowrisk ROIs was only 3.0%, significantly lower than the proportion of expected BMs. Yanagihara et al [18] also found that the brainstem, bilateral thalamus, hippocampus, parahippocampal gyrus, amygdala, and temporal pole showed BM involvement at a rate of 4.83%, and these low-risk ROIs may be avoided when treating with WBRT. However, Yanagihara et al did not report the proportion of patients with BMs in their low-risk ROIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the proportion of observed BMs in lowrisk ROIs was only 3.0%, significantly lower than the proportion of expected BMs. Yanagihara et al [18] also found that the brainstem, bilateral thalamus, hippocampus, parahippocampal gyrus, amygdala, and temporal pole showed BM involvement at a rate of 4.83%, and these low-risk ROIs may be avoided when treating with WBRT. However, Yanagihara et al did not report the proportion of patients with BMs in their low-risk ROIs.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of this study was to determine the low-risk and high-risk BM areas through the analysis of [18,20] have reported a difference in the risk of metastasis in different sub-structures of the brain; however, these studies divided the brain into several ROIs, thus, making it difficult to apply this approach in clinical practice. In this study, the whole brain was divided into 11 structures: the frontal lobe, parietal lobe, occipital lobe, temporal lobe, insula, internal structures and the diencephalon, brainstem, cerebellar hemispheres, vermis, corpus callosum, and pituitary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quattrocchi et al [ 11 ] have highlighted the non-uniform spatial distribution of BMs in patients with breast and lung cancer patient by using MRI scans. One recent study has demonstrated that several critical brain structures have a low risk of developing BMs, however, only 19 cases (6.9%) of BMs were from SCLC [ 13 ]. Yet, there is still uncertainty about results.…”
Section: Introductionmentioning
confidence: 99%
“…The voxel-wise analysis additionally found the differences of BMs volume according to various brain areas and primaries, while also implying the heterogeneity of BMs. Compared to the preferred distribution of infratentorial regions, the hippocampus was demonstrated to have a low risk of developing BMs [ 10 , 36 ]. There was a remarkably low proportion of hippocampus BMs in Figure 3 .…”
Section: Discussionmentioning
confidence: 99%